2007
DOI: 10.1211/jpp.59.4.0017
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis dracunculifolia, the main botanical source of Brazilian green propolis, displays antiulcer activity

Abstract: Baccharis dracunculifolia is the most important botanical source of Southeastern Brazilian propolis, known as green propolis for its colour. In a previous study, we described the gastric protective effect of the hydroalcoholic extract of Brazilian green propolis. We therefore wanted to investigate the possibility of using B. dracunculifolia extract for antiulcer treatment. This study was undertaken to evaluate the anti-ulcerogenic property of hydroalcoholic extract of B. dracunculifolia aerial parts. The HPLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 35 publications
3
59
0
12
Order By: Relevance
“…Besides, B. dracunculifolia is the most important botanical source of Southeastern Brazilian propolis, known as green propolis for its color (Marcucci et al, 1998;Park et al, 2002). Previous works have described the antiulcer activity of green propolis and B. dracunculifolia hydroalcoholic extract (Lemos et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, B. dracunculifolia is the most important botanical source of Southeastern Brazilian propolis, known as green propolis for its color (Marcucci et al, 1998;Park et al, 2002). Previous works have described the antiulcer activity of green propolis and B. dracunculifolia hydroalcoholic extract (Lemos et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Cinnamic acid derivatives and flavonoids were frequently reported in Brazilian propolis, which may be associated to antiulcer activity in green propolis (Lemos et al, 2007), while flavonoids such as C-glycosylflavones have been rarely identified. According to Righi et al (2011), a C-glycosylflavone was referred, for the first time, in propolis, by studying the Brazilian red propolis.…”
Section: Discussionmentioning
confidence: 99%
“…Its leaf extracts have been used as an antipyretic, a stomachic, and a health tonic in Brazil (Menezes, 2005). Potent cytotoxic activity against leukemia cells and antiulcer activity have also been reported (Fukuda et al, 2006;Lemos et al, 2007;Massignani et al, 2008). It has been reported that this plant is a source of resin for Brazilian propolis (green propolis), because of the similarity of their chemical constituents (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 91%